Motion of Li+ in Nanoengineered LiBH4 and LiBH4:Al2O3 Comparison with the Microcrystalline Form. Issue 16 (24th October 2013) - Epp, Viktor; Wilkening, Martin
Abstract The introduction of structural disorder and large volume fractions of different kinds of interfaces enables the manipulation of ion dynamics in solids. Variable‐temperature solid‐state NMR relaxometry is highly useful to study Li+ jump processes. If carried out as a function of frequency, the resulting NMR relaxation rates also contain information on the dimensionality (1D, 2D, or 3D) of the diffusion process. Recently, NMR relaxometry has revealed the 2D nature of Li hopping in LiBH4, and thus this hydride is an interesting ion conductor for further diffusion studies on the spatially confined motion of Li spins. Here, nanocrystalline LiBH4 and the two‐phase analogue LiBH4:Al2O3, which are prepared by ball milling, serve as interesting model systems to track the changes in NMR relaxation rates with respect to coarse‐grained, thermodynamically stable LiBH4. This reveals that interface (nano)engineering influences the hexagonal‐to‐orthorhombic phase transition and thus alters the ion‐transport properties of Li in one‐ and two‐phase LiBH4 towards higher diffusivities at lower temperatures.